Pretensions of objectivity toward a criticism of Biblical criticism - Morrow, Jeffrey L. 1978- (Pickwick Publications, 2019)
Modern historical biblical criticism, while having many strengths, often operates under the pretensions of objectivity, as if such scholarship were neutral and disinterested. Examining the history and roots of modern biblical scholarship shows that such objectivity is elusive, and was never intended by the method's earliest practitioners. Building upon his earlier work in Three Skeptics and the Bible and Theology, Politics, and Exegesis, Morrow continues this historical investigation into the political and philosophical roots of modern biblical criticism in Pretensions of Objectivity, in the hope of developing a criticism of biblical criticism and of making space for theological exegesis